Corrosion Behavior of V2AlC and Cr2AlC Compared with SS 316L in NaOH at Four Temperatures - Anaee, Rana A.; Al-Ghaban, Ahmed M.; Faleh, Russul F. (Al-Khwarizmi Engineering Journal, 2014)
Abstract This work involves the manufacturing of MAX phase materials include V2AlC and Cr2AlC using powder metallurgy as a new class of materials which characterized by regular crystals in lattice. Corrosion behavior of these materials was investigated by Potentiostat to estimate corrosion resistance and compared with the most resistant material represented by SS 316L. The experiments were carried out in 0.01N of NaOH solution at four temperatures in the range of 30–60oC. Polarization resistance values which calculated by Stern-Geary equation indicated that the MAX phase materials more resistant than SS 316L. Also cyclic polarization tests confirmed the resistivity of MAX phase materials through disappears of hysteresis loop. Key word: MAX phase materials, Corrosion behavior, V2AlC, Cr2AlC.